Space-time : an introduction to Einstein's theory of gravity - Allday, Jonathan (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
"This book, suitable for interested post-16 school pupils or undergraduates looking for a supplement to their course text, develops our modern view of space-time and its implications in the theories of gravity and cosmology. While aspects of this topic are inevitably abstract, the book seeks to ground thinking in observational and experimental evidence where possible. In addition, some of Einstein's philosophical thoughts are explored and contrasted with our modern views. Written in an accessible yet rigorous style, Jonathan Allday, a highly accomplished writer, brings his trademark clarity and engagement to these fascinating subjects, which underpin so much of modern physics. Features: Restricted use of advanced mathematics, making the book suitable for post-16 students and undergraduates Contains discussions of key modern developments in quantum gravity, and the latest developments in the field, including results from the Laser Interferometer Gravitational-Wave Observatory (LIGO) Accompanied by appendices on the CRC Press website featuring detailed mathematical arguments for key derivations"--
Four keystones -- The road to relativity -- The theory of special relativity -- Space-time -- Mass, energy and dust -- Generalising relativity -- The theory of general relativity -- Weak field gravitation -- Space-time in the general theory -- Black holes -- Gravity waves -- Cosmology -- Quantum considerations.
OCLC-licensed vendor bibliographic record.
Keywords: General relativity (Physics); Space and time; Quantum gravity; SCIENCE / Energy; SCIENCE / Mechanics / General; SCIENCE / Physics / General; SCIENCE / Astrophysics & Space Science; SCIENCE / Physics; MATHEMATICS / Recreations & Games